Collaborative Professional Development in Subject Teacher Forums: A Phenomenological Study of Science Teachers - Rivana Usgianti; Nurtanio Agus Purwanto; Slamet Lestari (Journal of Educational Sciences, 2026)
Improving teachers’ instructional performance is crucial for enhancing educational quality, especially during curriculum reforms. Musyawarah Guru Mata Pelajaran (MGMP) functions as a professional forum that supports collaborative learning and teacher development. This study examines the implementation of the science teachers’ MGMP in Indragiri Hilir, Indonesia, identifies participation challenges, and explores its contribution to instructional performance. A qualitative phenomenological approach was employed using interviews, observations, and document analysis. Data were collected from ten informants, including three school principals, six science teachers, and one MGMP coordinator. Data credibility was ensured through triangulation, while thematic analysis was used to interpret participants’ experiences. The findings show that MGMP is implemented through a hybrid model, enabling teacher participation despite geographical constraints. However, its effectiveness is affected by transportation difficulties, limited internet access, administrative workload, and uneven participation. MGMP contributes to improved lesson planning, instructional strategies, implementation of the Merdeka Curriculum, and contextual instructional innovation through collaborative learning and professional knowledge sharing. Teachers also demonstrate adaptive participation by engaging in self-directed learning and peer collaboration despite existing limitations. The study concludes that MGMP serves as a context-dependent professional learning community whose effectiveness is shaped by institutional support, contextual challenges, and teacher agency.